1975
DOI: 10.2134/agronj1975.00021962006700060020x
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility of Rhizobium japonicum with Chemical Seed Protectants1

Abstract: The literature on the compatibility of Rhizobium sp. with seed protectant chemicals is controversial because of variation in methods and the lack of quantitative data. The present study was planned to develop a reliable quantitative method of measuring compatibility of Rhizobium japonicum with seed‐applied fungicides. The effect of four seed protectant chemicals on survival of R. japonicum on soybean (Glycine max L. Merr. cv. ‘Hark’) seed was studied in laboratory growth chamber experiments. The chemicals test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
1
6

Year Published

1985
1985
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 2 publications
2
29
1
6
Order By: Relevance
“…The observations in this experiment indicated that the fungicide treatments had no effect on the assessed field pea parameters in most cases, caused negative effects in a few cases and had few positive effects. The lack of effect of Thiram on field pea nodulation and seed yield agrees with results on field pea (Dunfield et al 2000), chickpea (Kyei-Boahen et al 2001) and soybean (Wrobel 1963;Mikaly and Vincent 1969;Curley and Burton 1975), but not with the observations of reduced nodulation in field pea (Rennie et al 1985) and soybean (Tu 1980). Wrobel (1963) and Dunfield et al (2000) observed that fungicides containing Thiram did not affect nodulation and yield.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The observations in this experiment indicated that the fungicide treatments had no effect on the assessed field pea parameters in most cases, caused negative effects in a few cases and had few positive effects. The lack of effect of Thiram on field pea nodulation and seed yield agrees with results on field pea (Dunfield et al 2000), chickpea (Kyei-Boahen et al 2001) and soybean (Wrobel 1963;Mikaly and Vincent 1969;Curley and Burton 1975), but not with the observations of reduced nodulation in field pea (Rennie et al 1985) and soybean (Tu 1980). Wrobel (1963) and Dunfield et al (2000) observed that fungicides containing Thiram did not affect nodulation and yield.…”
Section: Discussionsupporting
confidence: 76%
“…It also appeared to be relatively non-lethal to seed-applied bacterial inoculant in a study by Mikaly and Vincent (1969), and out of the pesticides tested it possessed the lowest toxicity toward rhizobia. Similarly, seed treatment with Thiram had no effect on rhizobial numbers on the seed or nodule numbers on the roots (Curley and Burton 1975).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Bromfield et al (1986) and Vance & Graham (1995) emphasize the importance of understanding the ecology and characteristics of indigenous rhizobia populations as a prerequisite for inoculant establishment and persistence. Characteristics such as: antibiotic resistance (Mueller et al, 1988), fungicide resistance (Curley & Burton, 1975), low pH tolerance (Munns & Keyser, 1981;Wood et al, 1988), drought and high temperatures tolerance (Munevar & Wollum II, 1981;Graham, 1992), bacteriocin production (Schwinghamer & Brockwell, 1978) are considered in the selection of rhizobial strains with high adaptability in regions with adverse conditions. These properties could explain their saprophytic persistence (Frioni, 1990(Frioni, , 1999.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the use of fungicides has been shown to be incompatible with successful nodulation and N, fixation by seed-applied rhizobia (Curley and Burton 1975;Graham et al 1980), particularly in Canadian soils containing no indigenous rhizobia (see Rennie and Dubetz (1984), Rennie et al (1985) The '5N content of the plant material was de-termined by LiOBr conversion of NHo* to N, (Ross and Manin 1970;Porter and O'Deen 1977) followed by analysis of r5N''4N ratios on a VG Micromass 602D isotope ratio mass spectrometer. All isotope terminology was according to Rennie et al (1978).…”
mentioning
confidence: 99%